SOCIAL MEDIA AND DUAL CAREER PROMOTION FOR SPORTS HIGH SCHOOL STUDENTS - Onose Ionuț; Abalasei Beatrice Aurelia; Onose Raluca Mihaela (Sport şi Societate)
Human communication is achieved with the help of the interaction between two types of relationships: direct (when we talk about interpersonal communication) and indirect (when technological support also intervenes in mediating communication).Nowadays, social media is spreading all over the world with the help of digital progress, which opens new approaches to a multitude of platforms and applications (Gabelaia, 2019). Because social media catalyzes the transmission of information between people, allowing them to amplify their voices and reach large audiences in fractions of a second and at no cost (Kocak &Kibris, 2022), it follows that social media is becoming an important factor in daily life. In the present research, it was analyzed which social network is, from the subjects' point of view, the most suitable to promote the phrase "dual career" in the online environment. The Levene's Test for equality of variances and the Chi-square Test of Independence were used to determine whether there were associations between the responses obtained. The conclusions of the research are obvious: there is a social network that can successfully promote the dual career of athletes among young people.